2017
DOI: 10.26858/est.v3i3.3758
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Teacher Professional Competence and Natural Science Learning Achievement in Elementary School

Abstract: This present study aims at investigating the correlation between teachers 0.2560 (25.60%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Research from Förtsch, e al, (2016) showed that the competence of biology teachers in the aspects of pedagogical content knowledge and cognitive content knowledge of neurological topics can activate biology learning, thus influencing student learning achievement. This is in line with researchs by Ardiawan (2017) and Fauth et al, (2019) which showed that there was a significant influence between teacher competence, namely the mastery of standard material competencies for students on student achievement in science subjects. Competencies not mastered by the teacher will be less likely to be mastered by students and the most appropriate way of developing a learning continuum, based on this view, is the practitioners' focus of learning.…”
Section: Learning Continuum Developmentsupporting
confidence: 91%
“…Research from Förtsch, e al, (2016) showed that the competence of biology teachers in the aspects of pedagogical content knowledge and cognitive content knowledge of neurological topics can activate biology learning, thus influencing student learning achievement. This is in line with researchs by Ardiawan (2017) and Fauth et al, (2019) which showed that there was a significant influence between teacher competence, namely the mastery of standard material competencies for students on student achievement in science subjects. Competencies not mastered by the teacher will be less likely to be mastered by students and the most appropriate way of developing a learning continuum, based on this view, is the practitioners' focus of learning.…”
Section: Learning Continuum Developmentsupporting
confidence: 91%
“…Furthermore, teachers are required to have the ability to teach and role professionally as well as multifunction in creating an effective learning atmosphere. Thus, professional competence is one of the basic skills that a teacher must have (Ardiawan, 2017;Sugiharti, 2016).…”
Section: Teachers' Job Skillsmentioning
confidence: 99%
“…In accordance with the paramount of pedagogical competence, teachers as a professional profession are acquired to develop it in order to reach quality in terms of education as well as human resources, Ahmad and Setyaningsih (2012) reported that the teachers' position, as a professional element, should be improved and enhanced their role as the agent of the teaching-learning process in school. In addition, Ardiawan (2017) proved through his findings that there was a significant correlation between teachers' professional competence and students' learning achievement.…”
Section: Introductionmentioning
confidence: 97%